2022
DOI: 10.1242/bio.058852
|View full text |Cite
|
Sign up to set email alerts
|

Soluble receptor for advanced glycation end products protects from ischemia- and reperfusion-induced acute kidney injury

Abstract: The full-length receptor for advanced glycation end products (RAGE) is a multiligand pattern recognition receptor. High-mobility group box 1 (HMGB1) is a RAGE ligand of damage-associated molecular patterns that elicits inflammatory reactions. The shedded isoform of RAGE and endogenous secretory RAGE (esRAGE), a splice variant, are soluble isoforms (sRAGE) that act as organ-protective decoys. However, the pathophysiologic roles of RAGE/sRAGE in acute kidney injury (AKI) remain unclear. We found that AKI was mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In contrast to the study by Helena et al, plasma sRAGE levels were higher in septic patients with AKI than in those without AKI [19]. Recently, Taro et al found that the addition of recombinant sRAGE canceled hypoxia-induced inflammation and promoted cell viability in cultured murine tubular epithelial cells [20]. sRAGE administration might prevent renal tubular damage in ischemia/reperfusion-induced AKI models.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast to the study by Helena et al, plasma sRAGE levels were higher in septic patients with AKI than in those without AKI [19]. Recently, Taro et al found that the addition of recombinant sRAGE canceled hypoxia-induced inflammation and promoted cell viability in cultured murine tubular epithelial cells [20]. sRAGE administration might prevent renal tubular damage in ischemia/reperfusion-induced AKI models.…”
Section: Discussionmentioning
confidence: 76%
“…One clinical study showed that HMGB1, RAGE and interleukin (IL)-17 expression is increased in the liver tissue of HBV-ACLF patients, and the HMGB1 and RAGE interaction may contribute to inflammation of the liver, enhancing the expression of IL-17 (Jhun et al, 2015). Intriguingly, a recent experimental study showed that compared with wild-type control mice, mice lacking both RAGE and soluble isoforms (sRAGE) had more severe AKI, with enhanced renal tubular damage, macrophage infiltration, and fibrosis (Miyagawa et al, 2022). However, additional mechanisms or pathways are certainly involved, for example, autophagy-mediated HMGB1 release or the novel epigenetic role of HMGB1.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we have recently shown that acute kidney disease in a renal ischemia reperfusion injury model is exacerbated under RAGE-deficient conditions, and hypoxic stress downregulates the expression of both mRAGE and sRAGE/esRAGE in renal tubular cells [47]. Furthermore, recombinant sRAGE administration has been reported to have a renoprotective effect against tubular injury in a renal ischemia reperfusion injury model [47].…”
Section: Rage Isoformsmentioning
confidence: 97%
“…It has been previously reported that RAGE deficiency (i.e., absence of mRAGE and sRAGE) and treatment with purified recombinant sRAGE in mice lead to a protective effect in organs under various pathological conditions, such as acute lung injury, diabetic atherosclerosis, kidney diseases, Alzheimer's disease, and septic shock [2,5,19,55]. In contrast, we have recently shown that acute kidney disease in a renal ischemia reperfusion injury model is exacerbated under RAGE-deficient conditions, and hypoxic stress downregulates the expression of both mRAGE and sRAGE/esRAGE in renal tubular cells [47]. Furthermore, recombinant sRAGE administration has been reported to have a renoprotective effect against tubular injury in a renal ischemia reperfusion injury model [47].…”
Section: Rage Isoformsmentioning
confidence: 97%
See 1 more Smart Citation